Second Five Year Plan (1956-61) Bombay State, Statement E2, Manpower Required Continuing Phase - Planning Commission (Planning Commission, 1956)
Manpower required Continuing Phase Head of Development/Scheme for additional Staff of Development Training of Staff of the Department of Agriculture Head of Development/Scheme- Expansion of Training in Extension Work Head of Development/Scheme- Expansion of agriculture schools Head of Development/Scheme- Building for the college of Agriculture Poona Head of Development/Scheme- General Research Schools.
Bombay State